Healthcare resource utilization and costs associated with generalized myasthenia gravis: a retrospective matched cohort study using the National Health Insurance Research Database in Taiwan - Shen, Shih-Pei; Herr, Keira Joann; Liu, Yanfang; Yang, Chih-Chao; Tang, Chao-Hsiun (Frontiers in Neurology, 2023)
Background We estimated healthcare resource utilization (HRU) and costs in patients with generalized myasthenia gravis (gMG) in Taiwan. Methods This retrospective population-based, matched cohort study used the National Health Insurance Research Database to identify prevalent patients with gMG (cases) in 2019. In total, 2537 cases were matched (1:4) by age, sex, and urbanization level to 10148 randomly selected patients without gMG (comparators). A generalized linear regression model predicted the frequency of HRU and costs among service users. Costs attributable to gMG were obtained by subtracting all-cause HRU costs incurred by comparators from cases. Results The mean age of all patients was 54.99 years and 55.97% were female. Compared with comparators, cases had significantly higher rates of hypertension (33.03%/24.26%), diabetes mellitus (18.92%/11.37%), malignancies (16.00%/4.08%), cardiovascular disease (11.35%/8.12%), thyroid-related conditions (5.99%/1.16%), respiratory illness/disorders (4.38%/1.22%), and neurotic disorders (4.65%/2.6%). Amongst users of healthcare resources, cases had a mean 10 additional outpatient visits, 0.62 inpatient stays, and 0.49 emergency room visits in 2019 compared with comparators (p < 0.0001 for all). The mean (standard deviation) difference in all-cause healthcare costs between cases and comparators was NT 94997 (76431) [US 3133 (2521)], and was significantly higher for all categories (outpatient, inpatient, emergency room, drugs; p < 0.0001 for all). Among employed persons, 13.18%/7.59% of cases/comparators changed employment status during the study (p < 0.0001). Conclusion gMG presents a substantial burden on HRU and healthcare costs in Taiwan. A high attrition rate from full-time employment suggests additional societal costs. Improved treatments are needed to alleviate the burden of disease on individuals, healthcare systems, and economies.